Effect of thermal treatment of peats on composition and properties of humic acids; Solid fuel chemistry; Vol. 37, № 4 - Chukhareva N. V. Natalia Vyacheslavovna (2003, 2003)
Methods of acidic hydrolysis and thermal analysis were used to show that thermal treatment of peat at a temperature of up to 250 °C in a medium of its decomposition gases increases the thermal stability of humic acids dueto a change in the composition and structure of mainly the peripheral part of the macromolecule.